2016
DOI: 10.1038/sdata.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

ROCK signalling induced gene expression changes in mouse pancreatic ductal adenocarcinoma cells

Abstract: The RhoA and RhoC GTPases act via the ROCK1 and ROCK2 kinases to promote actomyosin contraction, resulting in directly induced changes in cytoskeleton structures and altered gene transcription via several possible indirect routes. Elevated activation of the Rho/ROCK pathway has been reported in several diseases and pathological conditions, including disorders of the central nervous system, cardiovascular dysfunctions and cancer. To determine how increased ROCK signalling affected gene expression in pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although ROCK actions on actin structures and cell morphology are well‐known (Rath & Olson, ; Julian & Olson, ), the same signaling pathway regulates gene transcription (Rajakylä & Vartiainen, ). Using RNA sequencing, expressions of 305 genes were found to be significantly ( P < 0.05) changed greater than twofold in 4HT‐treated ROCK1:ER‐expressing cells relative to GFP:ER‐expressing cells (Fig A, left), while 374 genes were significantly changed in ROCK2:ER versus GFP:ER‐expressing cells (Fig A, right), of which 285 were common changes (Fig B) (Rath et al , ). The greatest significantly increased fold‐changes were Mmp10 and Mmp13 , prostaglandin‐endoperoxidase synthase 2 ( Ptgs2 also known as Cox2 ), and Tenascin‐C ( Tnc ) (Fig A and ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although ROCK actions on actin structures and cell morphology are well‐known (Rath & Olson, ; Julian & Olson, ), the same signaling pathway regulates gene transcription (Rajakylä & Vartiainen, ). Using RNA sequencing, expressions of 305 genes were found to be significantly ( P < 0.05) changed greater than twofold in 4HT‐treated ROCK1:ER‐expressing cells relative to GFP:ER‐expressing cells (Fig A, left), while 374 genes were significantly changed in ROCK2:ER versus GFP:ER‐expressing cells (Fig A, right), of which 285 were common changes (Fig B) (Rath et al , ). The greatest significantly increased fold‐changes were Mmp10 and Mmp13 , prostaglandin‐endoperoxidase synthase 2 ( Ptgs2 also known as Cox2 ), and Tenascin‐C ( Tnc ) (Fig A and ).…”
Section: Resultsmentioning
confidence: 97%
“…Unprocessed RNA sequencing reads have been deposited as fastq files at the National Center for Biotechnology Information (NCBI) Sequence Reads Archive (SRA) with the reference SRP081135 (https://www.ncbi.nlm.nih.gov/sra/?term=srp081135) (Rath et al , ). In addition, a project overview has been submitted as the BioProject reference PRJNA327913 (http://www.ncbi.nlm.nih.gov/bioproject/?term=PRJNA327913) with a description of the BioSample reference SAMN05361890 (http://www.ncbi.nlm.nih.gov/biosample/?term=SAMN05361890).…”
Section: For More Informationmentioning
confidence: 99%
“…The results of the expression of RhoC and ROCK proteins shown by Western blot showed that RhoC silencing decreased ROCK protein expression, which is consistent with the finding of Rong et al who showed that the downstream effector molecule of RhoC is ROCK. Some studies have shown that RhoC activates ROCK by binding with ROCK and then phosphorylates the myosin light chain, participates in cell aggregation and fiber contraction, and promotes cell metastasis and infiltration …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that RhoC activates ROCK by binding with ROCK and then phosphorylates the myosin light chain, participates in cell aggregation and fiber contraction, and promotes cell metastasis and infiltration. 23 The MAPK signaling pathway exists widely in cells and is involved in many biological processes, such as cell growth, development, division, differentiation, and apoptosis. This pathway is also closely associated with the development and progression of multiple malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Sequence analysis and alignment was carried out as described in reference 12 . Quality control checks of raw RNA-Seq data files were done with fastqc v0.10.1 ( http://www.bioinformatics.babraham.ac.uk/projects/fastqc/ ) and fastq_screen v0.4.2 ( http://www.bioinformatics.babraham.ac.uk/projects/fastq_screen/ ).…”
Section: Methodsmentioning
confidence: 99%